2018
DOI: 10.1007/s11239-018-1744-9
|View full text |Cite
|
Sign up to set email alerts
|

Bariatric surgery in morbidly obese individuals affects plasma levels of protein C and thrombomodulin

Abstract: Obesity is associated with a prothrombotic milieu and an increased risk for thrombotic events. Bariatric surgery is the most effective treatment for obesity resulting in dramatic weight loss and reduced inflammation and extrinsic coagulation pathway activation. Blood samples were drawn from 60 patients undergoing Roux-en-Y gastric bypass surgery before and 1 year after the intervention. Protein C (PC), activated PC (APC), soluble thrombomodulin (TM), soluble E-selectin (E-Sel), prothrombin time (PT) and activa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
13
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 18 publications
(13 citation statements)
references
References 33 publications
(33 reference statements)
0
13
0
Order By: Relevance
“…This surgical intervention results in massive weight loss within the first year after surgery [14]. The weight loss is associated with dramatic changes such as a reduced inflammatory state and reduced hepatic stress [15,16,17].…”
Section: Introductionmentioning
confidence: 99%
“…This surgical intervention results in massive weight loss within the first year after surgery [14]. The weight loss is associated with dramatic changes such as a reduced inflammatory state and reduced hepatic stress [15,16,17].…”
Section: Introductionmentioning
confidence: 99%
“…Bariatric surgery has become an effective treatment for morbid obesity including an improvement in glucose metabolism, insulin resistance, and reduction of proinsulin levels [7][8][9][10]. In addition to changes in the metabolic syndrome, bariatric surgery is also associated with a reduced inflammatory profile and amelioration of coagulation [11,12].…”
Section: Introductionmentioning
confidence: 99%
“…Contrastingly, it has also been reported that 1 year after gastric bypass surgery, antithrombotic protein levels are also lower. 14 Future PK-pharmacodynamic (PD) studies should evaluate influence of obesity and weight loss on haemostatic balance to establish its relevance.…”
Section: Discussionmentioning
confidence: 99%